Selective electro-oxidation of phenol to 1,4-hydroquinone employing carbonaceous electrodes: surface modification is the key - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2022)
The oxidation of phenol leading to 1,4-hydroquinone with high conversion, remarkable selectivity and an excellent yield (87% isolated) has been accomplished under electrolytic conditions in an aqueous medium employing carbon-based electrodes. To achieve this, various factors such as electrode stability, repeatability, and the type of product formed by the electrochemical oxidation of phenol have been investigated using cyclic voltammetry first and then organic transformations under optimized conditions were accomplished by constant current electrolysis. The voltammetric data clearly show that electrochemically generated intermediates passivate the surface of the typically used electrodes, leading to a decrease in their activity, which is a major problem concerning the transformation of phenol electro-oxidation to an industrially adaptable process. In this work, it is established that such difficulties could be circumvented using surface modified carbonaceous electrodes having disordered graphene-like structures and oxygen functional groups. It is also demonstrated that surface modified reticulated vitreous carbon (RVC) based electrodes could be used for electro-oxidation of phenol at a reasonably large scale. The electrolysis conditions have been optimized based on the mechanistic understanding leading to remarkable conversion of phenol with 87% selectivity to 1,4-hydroquinone.

An effective alliance for successful coupling: electrochemical alcohol oxidation mediated conversion of indoles to bis(indolyl)methanes - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (Journal of Applied Electrochemistry, 2025)
Electro-organic transformation of indoles to bis(indolyl)methanes (BIMs) has been successfully achieved by combining the electrochemical alcohol oxidation reaction (AOR) with indole coupling. The fact that it is the readily available alcohols and not the traditionally used aldehydes or ketones that provide the bridging -CH2- (methylene) for this transformation makes this path extremely attractive and valuable. The formation of aldehydes as reactive intermediates during the AOR has been dexterously utilized to achieve this transformation. Most gratifyingly, the transformation also can be carried out in water-alcohol mixtures and the yields and conversions are better than the most of the previously reported chemical catalytic transformations using specially designed metal complexes. Various substituted indoles were selectively converted to their corresponding BIMs in decent yields. This strategy could further be exploited for the synthesis of different natural products, including the much sought after deuterium substituted ones (as CD3OD is readily accessible), and other important biologically active alkaloids and drug molecules, etc.
Keywords: Alcohol oxidation reaction; Bis(indolyl)methanes; Direct alcohol fuel cell; Electroorganic transformations; Vibrindole A

pH-Controlled electrochemical hydroxylation of acetanilide into value-added active pharmaceutical ingredients: a dual pathway synthesis of paracetamol and hydroquinone - Baravkar, Mayur D.; Prasad, V. Bhagavatula L. (Journal of Chemical Sciences, 2026)
A novel pH-controlled electrochemical method has been developed for the selective conversion of acetanilide into two value-added products, i.e., paracetamol and hydroquinone, via dual and tunable reaction pathways. It is shown that by adjusting the pH, and varying the electrolyte and the reaction environment specific oxidative transformations could be favored, allowing fine control over product selectivity and yield. This entire process is carried out under mild ambient conditions, eliminating the need for hazardous oxidants, specialized catalysts, or high temperatures, thereby supporting green chemistry principles. The electrochemical process also demonstrated excellent functional group tolerance, high atom economy, and minimal waste generation, highlighting its environmental and economic benefits. Its operational simplicity and scalability make it an attractive alternative to traditional multi-step methods for producing key intermediates used in drug manufacturing, fine chemicals, active pharmaceutical ingredients, and the polymer industry. This work showcases the potential of strategic electrochemical pH modulation as a powerful tool for sustainable chemical synthesis utilizing electrochemical organic transformations.
Keywords: acetanilide; Electrochemical hydroxylation; Hydroquinone; paracetamol